El compartamiento financiero de las empresas socialmente responsables - M. J. Charlo Molina; Ismael Moya Clemente (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2010)
This paper analyses financial performance of companies considered as highly socially responsible. For this purpose, companies that compose the Spanish sustainability index FTSE4Good IBEX (as well as other IBEX indices) are examined. Two basic results can be highlighted: first, stocks of companies that are socially responsible earn returns on excess over systematic risk, making them investment-attractive. Second, they have a higher systematic risk.
Keywords: G30; M14; 330; corporate social responsibility; socially responsible investment; FTSE4Good IBEX; sustainability index; ethical alpha